Design and Evaluation of Diltiazem Hydrochloride Microspheres Achieved by Spray Drying Method - Kamble, Shubham; Kajale, Archana D.; Kothari, Prafful P.; Kherade, Monika; Rasala, Tirupati (Pharmaceutical Science: New Insights and Developments Vol. 4, 2025)
Microencapsulation technology plays a transformative role in drug delivery systems, facilitating controlled release formulations. In this study, Diltiazem Hydrochloride was encapsulated using various natural and synthetic polymers, including Guar Gum, Xanthan Gum, Eudragit L100, Eudragit S100, and HPMC K4M, with a focus on optimizing the formulation via spray drying. The formulation F6, employing Eudragit L100 at a 1:2 drug-to-polymer ratio in isopropyl alcohol, demonstrated the most favorable release profile, achieving 100.44% cumulative drug release over 12 hours, indicative of a controlled release mechanism. Other formulations, including those with HPMC K4M, Guar Gum, and Xanthan Gum, failed to exhibit similar release characteristics. Comprehensive evaluations revealed that all the formulations maintained drug content uniformity between 60-70%, with the optimized batch exhibiting 70% uniformity and following zero-order kinetics. In vitro, release studies were conducted in a dissolution medium maintained at physiologically relevant conditions, and various kinetic models were employed to analyze drug release mechanisms. Scanning Electron Microscopy confirmed the spherical morphology of the microspheres, emphasizing their uniformity and structural integrity. Fourier Transform Infrared Spectroscopy was performed to assess polymer-drug compatibility, ensuring no adverse interactions. Overall, the study underscores the potential of spray-dried Eudragit L100 microspheres for enhanced, controlled drug delivery of Diltiazem Hydrochloride, contributing valuable insights into the field of pharmaceutical formulations.